ISLAM DAN PEKERJAAN SOSIAL - Zulkipli Lessy (Jurnal Sosiologi Reflektif, 2015)
Islamic theology and the fie pillars of Islam have historical and current roles in enhancing Islamic social work practices in Muslim communities. These effects are explored by means of literature review and via comparisons among Muslim populations and other religious followers and with an examination of the theology of Shi’i Muslims and Sunni Muslims. Basic concepts of Islam, such as shahada (testimony), prayers, fasting, zakat, and pilgrimage, are recommended for use by Muslim social workers in their practice with Muslim clients.